Cisplatin-Induced Anorexia and Pica Behavior in Rats Enhanced by Chronic Stress Pretreatment - Guo, Zhijun; Duan, Jingjing; Chen, Yitian; Cai, Weijia; Yang, Chenghua; Yang, Zhen; Liu, Xiufeng; Xu, Feng (Frontiers in Pharmacology, 2022)
Background: Chemotherapy-induced nausea and vomiting severely impairs the treatment and prognosis of cancer patients . Depressive mood disorder might aggravate nausea and vomiting in cancer patients, however, the role of vomit-related molecules involved in process is still not well elaborated. Methods: The study was carried on based on chronic unpredictable mild stress induced depressive-like phenotype model and cisplatin-induced vomit-like pica model establishment. Forty male Sprague Dawley rats were randomized into non-treated control group and chronic stress group which were exposed to 8 weeks of stress. Each group were then sub-divided into vehicle subgroup (n=10) and pica subgroup (n=10) which were given cisplatin to induce vomit-like pica. Kaolin and food intake were recorded after cisplatin administration. Medulla oblongata and ileum tissue samples were obtained. Vomit-related molecule (5-HT, DA, SP, AEA) were detected with ELISA kit. Vomit-related receptor (5-HT3R, DA2R, NK1R, CB1R) in tissues were assayed for mRNA and protein expression by qRT-PCR and Western blotting. Results: Behavioral test and sucrose preference validated that depression-like phenotype were established successfully. Kaolin consumption test confirmed that chronic stress aggravated anorexia and vomit-like behavior. Vomiting-related molecules data showed that chronic stress increased 5-HT and SP levels in medulla oblongata. Vomiting-related receptor expression data showed that chronic stress up-regulated 5-HT3R, DA2R, NK1R expression, and down-regulated CB1R expression in medulla oblongata. However, chronic stress down-regulated 5-HT3R, DA2R, NK1R expression, and up-regulated CB1R expression in ileum. Conclusion: Chronic stress aggravates anorexia and vomiting progress which might be via altering vomit-related molecule level and expression in central nervous system.